Network Pharmacology and Mechanism Studies of the Protective Effect of Ginseng against Alzheimerʼs Disease Based on Aβ Pathogenesis - Liu, Jinman; Yu, Wenqian; Ma, Cuiru; Li, Tianyao; Liang, Yong; Su, Shijie; Zhong, Guangcheng; Xie, Zhouyuan; Wu, Qiqing; Chen, Jiaxin; Wang, Qi (Planta Medica, 2023)
Alzheimerʼs disease (AD) is a critical neurodegenerative disease that manifests as progressive intellectual decline and is pathologically characterized by a progressive loss of neurons in the brain. Despite extensive research on this topic, the pathogenesis of AD is not fully understood, while the beta-amyloid (Aβ) hypothesis remains the dominant one and only a few symptomatic drugs are approved for the treatment of AD. Ginseng has been widely reported as an effective herbal medicine for the treatment of neurodegenerative diseases such as dementia. Therefore, we explore the protective effects of ginseng in AD by a network pharmacological approach based on the pathogenesis of Aβ. Twenty-one major ginsenosides are screened based on ultraperformance liquid chromatography-mass spectrometry/mass spectrometry (HPLC-MS/MS) data. Among them, MAPK8, MAPK9, BACE1, FLT1, CDK2, and CCR5 are the core targets. By molecular docking and validation with the in vitro cell model APPswe-SH-SY5Y, we find that ginsenosides Rg3 and Ro have good neuroprotective effects and can reduce the expression of Aβ1 – 42 in APPswe-SH-SY5Y. Finally, through RT-qPCR experiment, we find that ginsenoside Rg3 targeted MAPK8, FLT1, and CCR5, while ginsenoside Ro targeted MAPK8, MAPK9, FLT1, and CCR5 for its potential anti-AD efficacy.
Keywords: Ginseng; Araliaceae; Alzheimerʼs disease; beta-amyloid; network pharmacology; targets